Itaconate confers tolerance to late NLRP3 inflammasome activation - Bambouskova, Monika; Potuckova, Lucie; Paulenda, Tomas; Kerndl, Martina; Mogilenko, Denis A.; Lizotte, Kate; Swain, Amanda; Hayes, Sebastian; Sheldon, Ryan D.; Kim, Hyeryun; Kapadnis, Unnati; Ellis, Abigail E.; et al. (Cell reports (Cambridge), 2021)
Itaconate is a unique regulatory metabolite that is induced upon Toll-like receptor (TLR) stimulation in myeloid cells. Here, we demonstrate major inflammatory tolerance and cell death phenotypes associated with itaconate production in activated macrophages. We show that endogenous itaconate is a key regulator of the signal 2 of NLR family pyrin domain containing 3 (NLRP3) inflammasome activation after long lipopolysaccharide (LPS) priming, which establishes tolerance to late NLRP3 inflammasome activation. We show that itaconate acts synergistically with inducible nitric oxide synthase (iNOS) and that the ability of various TLR ligands to establish NLRP3 inflammasome tolerance depends on the pattern of co-expression of IRG1 and iNOS. Mechanistically, itaconate accumulation upon prolonged inflammatory stimulation prevents full caspase-1 activation and processing of gasdermin D, which we demonstrate to be post-translationally modified by endogenous itaconate. Altogether, our data demonstrate that metabolic rewiring in inflammatory macrophages establishes tolerance to NLRP3 inflammasome activation that, if uncontrolled, can result in pyroptotic cell death and tissue damage. [Display omitted] •Itaconate tolerizes macrophages to late NLRP3 inflammasome (i.e., long LPS priming)•Itaconate acts downstream of ASC, affecting caspase-1/GSDMD interplay•Late inflammasome require GSDMD for caspase-1 activation; GSDMD-Cys77 is itaconated•iNOS and IRG1 jointly establish late inflammasome tolerance Bambouskova et al. determine the in vitro phenotype of Irg1−/− macrophages and define itaconate as a key regulator of tolerance to late NLRP3 inflammasome activation.